2014
DOI: 10.1590/s0102-86502014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hemorrhagic effect of hydro-alcoholic extract of the leaves of Mikania glomerata in lesions induced by Bothrops jararaca venom in rats

Abstract: Conception, design, intellectual and scientific content of the study; critical analysis; final approval. ABSTRACT PURPOSE:To investigate the effects of hydroalcoholic leaf extract of Mikania glomerata Spreng (Asteraceae) on the activity of Bothrops jararaca snake venom in Wistar rats. METHODS:Fifty four rats Wistar were divided into six groups of nine animals in each: control treated with saline; control treated with B. jararaca venom; control treated with M. glomerata extract; B. jararaca venom incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
3
3
0
1
Order By: Relevance
“…These findings agree with experimentally identified anti-inflammatory and antihemorrhagic properties of the Mikania genus against myotoxic, neurotoxic, and inflammatory effects of snake venoms [2]. The above observations are further supported by the findings of other studies in rats that revealed 80% reduction in hemorrhage area following intradermal injection of Bothrops venom and Mikania extract administration [14], and reduction of inflammatory cells, edema, and hemorrhagic halo 3 h after administration of B. jararaca venom and Mikania leaf extract [10].…”
supporting
confidence: 90%
“…These findings agree with experimentally identified anti-inflammatory and antihemorrhagic properties of the Mikania genus against myotoxic, neurotoxic, and inflammatory effects of snake venoms [2]. The above observations are further supported by the findings of other studies in rats that revealed 80% reduction in hemorrhage area following intradermal injection of Bothrops venom and Mikania extract administration [14], and reduction of inflammatory cells, edema, and hemorrhagic halo 3 h after administration of B. jararaca venom and Mikania leaf extract [10].…”
supporting
confidence: 90%
“…Our results are in line with researches that pointed the protective role of M. glomerata in the prevention of the oxidative lung damage in a coal dust exposure model [17] and reduction of inflammatory cells in lesions induced by Bothrops jararaca venom in rats [26].…”
Section: Discussionsupporting
confidence: 92%
“…Mikania spp. has provided a wide range of promising phamacological activities and it can be described as having expectorant, anti-inflammatory, bronchodilator, anti-hemorrhagic, antiasthmatic, analgesic, anti-mutagenic, trypanocidal, antimicrobial, antifungal, antiulcerogenic, muscle relaxant, and antirheumatic properties (Muelas-Serrano et al, 2000;Paul et al, 2000;Gasparetto et al, 2010;Pérez-Amador et al, 2010;Mourão et al, 2014;Ríos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%